Re: Ultrasound for monitoring controlled ovarian stimulation: a systematic review and meta‐analysis of randomized controlled trials. W. P. Martins, C. V. R. Vieira, D. M. Teixeira, M. A. P. Barbosa, L. A. Dassunção and C. O. Nastri. Ultrasound Obstet Gynecol 2014; 43: 25–33. (January 2014) - Drakeley, A.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014:43:25–33